Comparison of two surgical techniques for creating an acute myocardial infarct in rats - Luiz Guilherme Achcar Capriglione; Fabiane Barchiki; Gabriel Sales Ottoboni; Nelson Itiro Miyague; Paula Hansen Suss; Carmen Lúcia Kuniyoshi Rebelatto; Cláudia Turra Pimpão; Alexandra Cristina Senegaglia; Paulo Roberto Brofman (Brazilian Journal of Cardiovascular Surgery, 2014)
Objective: To perform a comparative assessment of two surgical techniques that are used creating an acute myocardial infarc by occluding the left anterior descending coronary artery in order to generate rats with a left ventricular ejection fraction of less than 40%. Methods: The study was completely randomized and comprised 89 halothane-anaesthetised rats, which were divided into three groups. The control group (SHAM) comprised fourteen rats, whose left anterior descending coronary artery was not occluded. Group 1 (G1): comprised by 35 endotracheally intubated and mechanically ventilated rats, whose left anterior descending coronary artery was occluded. Group 2 (G2): comprised 40 rats being manually ventilated using a nasal respirator whose left anterior descending coronary artery was occluded. Other differences between the two techniques include the method of performing the thoracotomy and removing the pericardium in order to expose the heart, and the use of different methods and suture types for closing the thorax. Seven days after surgery, the cardiac function of all surviving rats was determined by echocardiography. Results: No rats SHAM group had progressed to death or had left ventricular ejection fraction less than 40%. Nine of the 16 surviving G1 rats (56.3%) and six of the 20 surviving G2 rats (30%) had a left ventricular ejection fraction of less than 40%. Conclusion: The results indicate a tendency of the technique used in G1 to be better than in G2. This improvement is probably due to the greater duration of the open thorax, which reduces the pressure over time from the surgeon, allowing occlusion of left anterior descending coronary artery with higher accuracy.